Inhibition of the production of mediators of inflammation by corticosteroids is a glucocorticoid receptor-mediated process - G. S. Madretsma; A. P. M. van Dijk; C. J. A. M. Tak; J. H. P. Wilson; F. J. Zijlstra (Mediators of Inflammation)
In order to find an explanation for corticosteroid resistance we assessed whether inhibition by dexamethasone (DEX) of the stimulated production of TNF-∝, IL-6, PGE2 and LTB4 by peripheral blood mononuclear cells (MNC) depends on binding to the glucocorticoid receptor (GR), and whether it is determined by the number or the affinity of the GR of these cells. GR number and affinity of MNC were determined by means of a whole cell DEX binding assay. MNC were incubated with DEX and LPS or A23187 in the absence or presence of RU486, a potent steroid antagonist. DEX caused a concentration dependent inhibition of TNF-∝, IL-6 and PGE2 production but had no effect on LTB4 production. RU486 significantly blocked the effect of DEX, but no correlations were found between the inhibition of mediator release and the Kd or receptor number.